Solid organ transplant patients: are there opportunities for antimicrobial stewardship?. Issue 6 (18th May 2016) - So, Miranda; Yang, Daisy Yu; Bell, Chaim; Humar, Atul; Morris, Andrew; Husain, Shahid
Abstract: Objective: Rising incidence of Clostridium difficile and multidrug‐resistant organisms' infections and a dwindling development of new antimicrobials are an impetus for antimicrobial stewardship in organ transplant recipients. We sought to understand antimicrobial prescribing practices and identify opportunities for interdisciplinary collaboration among the transplant, antimicrobial stewardship, and infectious diseases teams. Methods: In 2013, two assessors conducted four real‐time audits on all antimicrobial therapy in transplant patients, assessing each regimen against stewardship principles established by the Centers for Disease Prevention and Control, supplemented by applicable transplant‐specific infection guidelines. Chi‐square test was used to compare stewardship‐concordant and stewardship‐discordant audit results relative to transplant infectious diseases consultation. Results: Analysis was performed on 176 audits. Fifty‐eight percent (103/176) received at least one antimicrobial, of which 69.9% (72/103) were stewardship‐concordant. Infections were confirmed or suspected in 52.3% (92/176). Of those, 98.9% (91/92) received antimicrobials, and 41.8% (38/91) were prescribed by transplant clinicians. Infectious diseases consultation was associated with more stewardship‐concordant prescriptions (78.5% vs. 59.6%, p = 0.03). The most common stewardship‐discordant categories were lack of de‐escalation, empiric antimicrobial spectrum being too broad, and therapy duration being too long. Conclusions: Opportunities exist for antimicrobial stewardship in transplant recipients, especially those who do not require infectious diseases consultation.